2019
DOI: 10.1111/febs.14803
|View full text |Cite
|
Sign up to set email alerts
|

Light‐controlled carotenoid transfer between water‐soluble proteins related to cyanobacterial photoprotection

Abstract: Carotenoids are lipophilic pigments with multiple biological functions from coloration to vision and photoprotection. Still, the number of water‐soluble carotenoid‐binding proteins described to date is limited, and carotenoid transport and carotenoprotein maturation processes are largely underexplored. Recent studies revealed that CTDHs, which are natural homologs of the C‐terminal domain (CTD) of the orange carotenoid protein (OCP), a photoswitch involved in cyanobacterial photoprotection, are able to bind ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 61 publications
(205 reference statements)
4
59
1
Order By: Relevance
“…We scrutinized the process of carotenoid uptake from membranes by CTDH and showed that ECN distribution is in a dynamic equilibrium which is shifted from the protein to membrane (35 vs. 65 %, respectively), permitting efficient delivery of carotenoids into membranes ( Figure 5). Moreover, light could be potentially used in order to activate the process of carotenoid delivery into membranes by CTDH from the photoconvertible OCP ( Figure S4) (24).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We scrutinized the process of carotenoid uptake from membranes by CTDH and showed that ECN distribution is in a dynamic equilibrium which is shifted from the protein to membrane (35 vs. 65 %, respectively), permitting efficient delivery of carotenoids into membranes ( Figure 5). Moreover, light could be potentially used in order to activate the process of carotenoid delivery into membranes by CTDH from the photoconvertible OCP ( Figure S4) (24).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of two keto-groups in CAN results in the most efficient carotenoid binding in the CTDH dimer, while ECN binding is apparently weaker. Since both types of CTDH can transfer carotenoids into other proteins we postulate that spontaneous monomerization of protein dimer occurs regardless of the carotenoid type (24). However, only CTDH monomers in which ketogroup of ECN loses connection with the protein give carotenoid an opportunity to escape another protein subunit and get to the membrane once again.…”
Section: Fig 5 Proposed Model For Ctdh-mediated Carotenoid Uptake Amentioning
confidence: 99%
See 3 more Smart Citations